1993
DOI: 10.1177/074391569101200208
|View full text |Cite
|
Sign up to set email alerts
|

Is There a General Conserving Consumer? A Public Policy Concern

Abstract: The authors conducted a survey to identify conservation activity among the general populace of a midsize Southwestern community to increase our understanding of those who do and do not engage in a broad section of environmentally friendly activities. Numerous self-reported behaviors were gauged and combined to form a composite measure representing the conserving consumer. They then explored both demographic and psychosocial variables as predictors of this self-reported composite scale of conservation. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(66 citation statements)
references
References 24 publications
2
61
0
Order By: Relevance
“…Despite this common conceptualization, however, the magnitude of the relationship between these two constructs is inconsistent at best (Boulstridge & Carrigan, 2000;Carrigan & Attalla, 2001;Manaktola & Jauhari, 2007), giving rise to the notion that environmental concern plays an equivocal role in the decision making processes surrounding environmental purchasing (Akehurst, Afonso, & Gonçalves, 2012;Fransson & Gärling, 1999;Pickett, Kangun, & Grove, 1993;Wearing, Cynn, Ponting, & McDonald, 2002). Thus, an unresolved issue in the literature is whether the relationship between environmental concern and environmental purchase intentions is conditional upon the existence of additional constructs.…”
Section: Introductionmentioning
confidence: 84%
“…Despite this common conceptualization, however, the magnitude of the relationship between these two constructs is inconsistent at best (Boulstridge & Carrigan, 2000;Carrigan & Attalla, 2001;Manaktola & Jauhari, 2007), giving rise to the notion that environmental concern plays an equivocal role in the decision making processes surrounding environmental purchasing (Akehurst, Afonso, & Gonçalves, 2012;Fransson & Gärling, 1999;Pickett, Kangun, & Grove, 1993;Wearing, Cynn, Ponting, & McDonald, 2002). Thus, an unresolved issue in the literature is whether the relationship between environmental concern and environmental purchase intentions is conditional upon the existence of additional constructs.…”
Section: Introductionmentioning
confidence: 84%
“…While it has been suggested that pro-environmental conduct has a tendency to spillover from one behaviour to another (Thøgersen 1999), some researchers have argued that when people engage in pro-environmental behaviour (perhaps a simple and painless step), they often use this to justify not doing other (perhaps more environmentally significant) things (Diekmann and Preisendörfer 1998;Schahn 1993). Yet other researchers emphasize the uniqueness of every pro-environmental behaviour and downplay the possibility that pro-environmental conduct in one area will have any implications-whether positive or negative-for the likelihood of acting proenvironmentally in different areas (McKenzie-Mohr et al 1995;Pickett et al 1993).…”
Section: An Overview Of Empirical Evidence On Spillovermentioning
confidence: 97%
“…The sample is not a random sample of Cairo inhabitants although it is deemed to be fairly representative of university students and high school teachers in the metropolis. Self-reported behaviors are surrogate indicators of actual activity and may misrepresent behavior patterns (Pickett et al, 1993). However, given the low awareness of environmental issues in Egypt and the low incidence of pro-environmental behaviors, it is unlikely that any socially desirable response bias occurred.…”
Section: Limitationsmentioning
confidence: 99%
“…In particular, the research seeks to identify the relationship between pro-environmental behavior and demographic variables, beliefs, values, and religiosity. The emphasis in the study is on behavior because progress toward solving environmental problems is likely to depend on environmentally beneficial behaviors more so than on environmental consciousness (Pickett et al, 1993). An important research question is whether an environmental ethic based in religion is present, and whether this could be used to further proenvironmental behaviors in Egypt, a country inhabited predominantly by Muslims.…”
Section: Introductionmentioning
confidence: 99%